La dynamique spatio-temporelle des prix immobiliers à différentes échelles : le cas des appartements anciens à Paris (1990-2003) - Marianne Guérois; Renaud Le Goix (Cybergeo, 2009)
In order to get a better understanding of the complex patterns in undergoing urban changes, this paper aims at studying property values, with an emphasis on methodological experimentation. Property values not only describe intrinsic characteristics of housing (hedonic pricing) but also the characteristics of place, assessed and perceived at different geographical levels (location in a city, social characteristics of the neighborhood, and these of the street). Prices changes also induce a powerful social filter in city core areas. In an experimental perspective at the lower local scale, this paper elaborates on an analysis of property values of housing in downtown Paris (1990-2003). In a context of dropping prices followed by a time of continuous and unparalleled growth of prices since 1997, we analyze the complexity of spatial shifts and adjustments of prices, so that we might identify underlying depreciation and valuation dynamics at a infra-neighborhood level. A first section reviews different time-patterns of prices change over the decade, with a special focus on resulting spatial patterns. We then discuss the dynamics of spatial dissimilarities in price patterns, such as fading, reinforcing and moving boundaries of prices. By the means of confronting methodological approaches (smoothing, discontinuity analysis), we give insights on the most significant spatial patterns of change in a time-series of housing prices. We promote this exploratory approach as an effort towards a better understanding of the complexity of spatial contexts in the formation of prices, as contexts and neighborhood effects are often roughly incorporated in price modeling as an externality in the valuation (i.e. hedonic pricing). In a general trend of price towards a greater homogeneity, contrasts and dissimilarities between neighborhoods move according to local planning policies and change in the image of a neighborhood. We observe on one hand a reinforcement of the core-periphery gradient and a continuous valorization of the city core, and on the other hand the increase of prices in the peripheries creates a greater heterogeneity and composites and contrasted local patterns.